Relationships between Emotional Intelligence, Leadership Behavior and Organizational Commitment with Organizational Readiness for Change in a Malaysian Institute of Higher Learning - Mohd Noordin, Norsidah (2008)
The purpose of this study was to investigate the relationships between emotional intelligence, leadership behavior (Transformational and Transactional) and organizational commitment (affective, normative and continuance) in influencing perceptions and responses of organizational readiness for change among the academic staff in a Higher learning Institution. Specifically, the study attempted (1) to determine the level of organizational readiness for change, organizational commitment, emotional intelligence and perceived leadership behavior exhibited in UiTM; (2) to determine the relationship between emotional intelligence, perceived leadership behavior, organizational commitment and organizational readiness for change; (3) to determine the contribution of the significant predictors variables towards explaining the variance of the criterion variables; (4) to determine whether organizational commitment is a moderator variable for the relationship between emotional intelligence, perceived leadership behavior and organizational readiness for change among the academic staff of UiTM. This is a descriptive-correlational research study. It was based on conceptual framework that combined part of adapted model from organizational development and change theory (Lewin, 1947, Burke-Litwin, 1992) and the Three-Component Model (TCM) of organizational commitment developed by Meyer and Allen (1991, 1997). A total of 168 academic staff of UiTM participated in this study. They were selected based on cluster sampling from the main and branch campuses through Malaysia. Data were collected using the survey method and were analyzed using both descriptive and inferential statistics. This study provided empirical evidences that the academic staff of UiTM perceived that the organization is ready for change. The findings also showed that generally the academic staff has high level of emotional intelligent competencies, moderate level organizational commitment and perceived their superiors having moderate transformational and transactional leadership style. In term of the relationships between dependent and the independent variables, the result revealed that there was a positive and moderate linear relationship between overall scores of emotional intelligence, its clusters scores and organizational readiness for change. Besides, there was a positive and moderate linear relationship between transformational, transactional leadership behavior and organizational readiness for change. The relationship between affective commitment and organizational readiness for change showed a positive and moderate linear relationship. However, there was positive and low linear relationship of normative and continuance commitment and organizational readiness for change. In terms of determining the contributions of the significant predictive power of emotional intelligence, transformational and transactional leadership behavior and the three-components of organizational commitment in explaining organizational readiness for change, the result revealed 44.1% of the variance in readiness for change is explained by emotional intelligence, organizational commitment and transactional leadership behavior, In determining the role of the organization commitment as a moderating variable, the finding shows that organizational commitment moderated the effects of transactional leadership on organizational readiness for change; and continuance commitment moderated the effects of transactional leadership on organizational readiness for change. Based on the results, the implications of the findings were discussed in the context of understanding the organization readiness for change and its implications to change management and adult learning and practices. Suggestions on how to enhance organizational readiness for change and avenues for future research were also provided in this discussion.